Herd Immunity: Does Social Media Affect Adherence to the CDC Childhood Vaccination Schedule? - Katherine Bolton; Kendall Memory; Cody McMillan (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Social Media can alter herd immunity by having a subtle yet pervasive impact on the adherence to the Childhood Vaccination Schedule recommended by the Center for Disease Control (CDC). Parents of children (newborn to young adults) utilize social media to acquire medical information such as the CDC’s Recommended Childhood Vaccination Schedule. Complying with anti-vaccination messages can result in parents not vaccinating their children, leading to a decline in the public’s herd immunity against known pathogens. However, there is a dearth of information about the possible impact of social media on herd immunity from childhood vaccination. Thus, this literature review will discuss the emerging themes from the current science in an effort to provide an initial understanding. In addition, the authors will provide a framework by which these themes demonstrate the ‘pitfalls’ of social media.